A review of the application of green walls in the acoustic field. Issue 2 (June 2022) - Yan, Feng; Shen, Jingjing; Zhang, Wuxia; Ye, Leiting; Lin, Xinfeng
Green wall technology, including green façades and living walls, presents a promising solution to encounter the negative impacts of noise pollution. Research and development of green walls are steadily progressing in multiple fields, including but not limited to the environmental, social, and economic areas. Compared to other themes, the number of acoustic studies of green walls is relatively low and lacks relevant review papers. The purpose of this paper is to give a systematic review of the application of green walls in the acoustic field and clarify the key factors that influence the acoustic performance of green walls and the main obstacles that obstruct the broader application of green walls. A total number of 34 papers published in the past 10 years are reviewed. This study identifies that the acoustic applications of green walls are mainly in four aspects, namely laboratory applications, outdoor applications, indoor applications, and audio-visual applications. Vegetation morphology and properties of substrates are the two crucial factors determining green facades and living walls' acoustic properties, respectively. High installation, operation, and maintenance costs and plant-induced problems are recognized as the main obstructions. A few possible topics are recommended for future study as well.